2012
DOI: 10.3945/jn.112.163824
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ʟ-Tryptophan Supplementation with Reduced Large Neutral Amino Acids Enhances Feed Efficiency and Decreases Stress Hormone Secretion in Nursery Pigs under Social-Mixing Stress

Abstract: Tryptophan (Trp), the rate-limiting substrate of serotonin [5-hydroxytryptoamine (5-HT)] synthesis in the brain, competes with large neutral amino acids (LNAA) to cross the blood-brain barrier. This study was designed to evaluate the effect of L-Trp supplementation on nursery pigs experiencing social-mixing stress and fed diets varying in LNAA concentrations. Forty-eight individually housed barrows at 6 wk of age were randomly allotted to 4 dietary treatments based on a 2 × 2 factorial arrangement, with L-Trp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 66 publications
(112 reference statements)
1
28
0
1
Order By: Relevance
“…This result supports our previous study (Shen et al, 2012a) indicated lowering LNAA further enhanced the improvement of feed efficiency by l-Trp supplementation of nursery pigs under social-mixing stress.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This result supports our previous study (Shen et al, 2012a) indicated lowering LNAA further enhanced the improvement of feed efficiency by l-Trp supplementation of nursery pigs under social-mixing stress.…”
Section: Discussionsupporting
confidence: 94%
“…Surprisingly, pigs fed a reduced LNAA diet supplemented with 0.7% l-Trp had lower PUN than pigs fed the diet supplemented with 0.8% l-Trp. This may be due to the 0.7% l-Trp supplemented reduced LNAA diet had a lower protein level compared with 0.8% l-Trp supplemented diet (Shen et al, 2012a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For hypothalamus analysis, samples were analyzed in duplicate within a single assay. Hypothalamus was measured for 5-HT concentration (validated for pigs by Shen et al, 2012) using a commercially available ELISA kit (Research & Diagnostics Systems, US), conforming to the manufacturer's instructions. The intra-and inter-assay variation coefficients of the kit were 3.2% to 5.3% and 8.1% to 9.3%, respectively.…”
Section: -Hydroxytryptamine In the Hypothalamusmentioning
confidence: 99%